Effects of Wage Parity between Canada and the United States on Canadian Economic Growth: Simulation Experiments with a Macro Model - Hiroki Tsurumi (Queen's University, Department of Economics, 1969)
This paper talks about the wage-parity issue which arose in 1968 when the United Auto Workers demanded wage-parity between Canadian and American workers in the automobile industry. Also, if wage-parity is introduced, what and how severe will be its effects on the prices and on Canadian economic growth. The present paper attempts to give some answers to this question.
Keywords: 330